Hypersensitivity to fluoroquinolones: The expression of basophil activation markers depends on the clinical entity and the culprit fluoroquinolone - Fernández, Tahia D. (Medicine (Baltimore), 2016)
Although fluoroquinolones (FQs) are generally well-tolerated antibiotics, increasing numbers of hypersensitivity reactions have been reported. These can be evaluated in vitro by basophil activation tests (BATs); however, sensitivity is not optimal. Many factors could influence sensitivity such as basophil activation markers. The objective of this study was to evaluate the influence of 2 different activations markers, CD63 and CD203c, on the sensitivity of BAT to FQ. We studied 17 patients with immediate allergic reactions to FQ. BAT was performed with moxifloxacin and ciprofloxacin using CD193 (CCR3) for basophil selection and CD203c or CD63 as activation markers. Stimulation with ciprofloxacin induced a significantly higher expression of CD63 in ciprofloxacin-allergic patients compared to moxifloxacin-allergic patients (P = 0.002). In patients allergic to moxifloxacin with anaphylactic shock, we have observed an increase in the percentage of cells that upregulate CD203c, whereas patients with anaphylaxis preferentially upregulate CD63. The best sensitivity–specificity was obtained using a cutoff of 3 and the culprit FQ, using CD203c for moxifloxacin-allergic patients (sensitivity = 36.4%; specificity = 94.4%), and CD63 for ciprofloxacin-allergic patients (sensitivity = 83.3%; specificity = 88.9%). A negative correlation was found between the upregulation of CD63 and CD203c and the time interval between the reaction occurrence and the performance of the test (Spearman r = −0.446; P < 0.001 for CD63 and Spearman r = −0.386; P < 0.001 for CD203c). The performance of BAT for FQ allergy must be optimized for each drug, taking into account possible differences in the stimulation mechanism that leads to the upregulation of different activation markers.